Serverless programming cookbook practical solutions to building serverless applications using Java and AWS - Kanikathottu, Heartin (Packt Publishing Ltd, 2019)
The serverless architecture allows you to build and run applications and services without having to manage the infrastructure which saves cost and improves scalability. In this book, you will learn to harness serverless technology to reduce production time, minimize cost and have the freedom to customize your code, without hindering functionality.